Are the firms' capital structure and performance related? Evidence from GCC economies - Shoaib Khan; Ameen Qasem (Cogent Business & Management, 2024)
This study examines the empirical relationship between the different leverage levels as a proxy of financing mix on the financial performance of the non-financial firms listed on capital markets in GCC economies. The study uses the pooled ordinary least squares regression (OLS), fixed and random effects regression, and feasible generalised least square (FGLS) regression to explore the relationship among variables on the data of GCC firms listed from 2011 to 2021. The results suggest that the capital structure considerably affects firms' performance. Findings refute the theoretical assumptions of Modigliani and Miller's debt irrelevance and debt-supporting theorem. The findings also contradict the debt-supporting benefits the agency and trade-off theory suggest. Empirically, short-term, long-term, and total debt adversely affect the return on assets, equity, and earnings per share. Control variables, growth opportunities, and size of the firm positively and asset tangibility negatively contribute to the performance. The results will support the managers in making performance-improving financing decisions. Lenders should improve ex-ante screening and ex-post monitoring to avoid possible defaults. Local and foreign investors should carefully examine the firms' debt levels before making investment decisions. Policymakers should focus on the flourishing of the bond markets to support privatisation and economic diversification. Our study is the first to use the recent data of GCC-listed firms to examine the impact of capital structure on firms' performance. Contributing to the literature gap will also lay a foundation for a more comparative study on corporate financing with alternative financial instruments.
Keywords: 650; Capital structure; firms; GCC economies; leverage; performance